Strategies in Developing Junior High School Students' Science Process Skills in the Material of Temperature, Heat, and Expansion - Wirayuda, Ricky Purnama; Salsabilla Nurma Yahya, Gita (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study aims to explore how teacher strategies enhance students' science process skills, particularly observation, graphing, and communication during physics learning on the topic of heat, temperature, and expansion at the junior high school level. Methodology: This study employs a naturalistic qualitative method aimed at exploring teachers' strategies in enhancing students' science process skills during physics lessons on temperature, heat, and expansion. Data were collected through interviews, and documentation, then analyzed descriptively to identify patterns and themes that reflect students' abilities in observation, communication, and data representation. Main Findings: The study found that teachers effectively foster students’ science process skills (SPS) in physics through varied strategies, including scientific approaches, step-by-step instruction, and cooperative learning. By integrating observation, graphing, and communication activities during laboratory sessions, teachers provided scaffolding, feedback, and peer collaboration. These strategies, supported by theories of Vygotsky, Bruner, and Ausubel, created an engaging and structured learning environment that promoted students’ active participation and scientific reasoning. Novelty/Originality of this study: This study presents a novelty through the use of informant triangulation involving teachers, laboratory assistants, and students, which is rarely applied in similar studies on science process skills (SPS). Three SPS indicators are systematically examined through four pedagogical strategies, supported by direct quotations that provide a contextual, comprehensive, and student-centered perspective in physics learning.